The influence of caffeine and carbohydrate coingestion on simulated soccer performance - Gant, N.; Ali, A.; Foskett, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Carbohydrate and caffeine are known to independently improve certain aspects of athletic performance. However,less is understood about physiological and performance outcomes when these compounds are coingested in a rehydration and carbohydrate-replacement strategy. The aim of this study was to examine the influence of adding a moderate dose of caffeine to a carbohydrate solution during prolonged soccer activity. Fifteen male soccer players performed two 90-min intermittent shuttle-running trials. They ingested a carbohydrate electrolyte solution (CON) providing a total of 1.8 g/kg body mass (BM) of carbohydrate or a similar solution with added caffeine (CAF; 3.7 mg/kg BM). Solutions were ingested 1 hr before exercise and every 15 min during the protocol. Soccer passing skill and countermovement-jump height (CMJ) were quantified before exercise and regularly during exercise. Sprinting performance, heart rate, blood lactate concentration (La) and the subjective experiences of participants were measured routinely. Mean 15-m sprint time was faster during CAF (p = .04); over the final 15 min of exercise mean sprint times were CAF 2.48 ± 0.15 s vs. CON 2.59 ±0.2 s. Explosive leg power (CMJ) was improved during CAF (52.9 ± 5.8 vs. CON 51.7 ± 5.7 cm, p = .03). Heart rate was elevated throughout CAF, and ratings of pleasure were significantly enhanced. There were nosignificant differences in passing skill, rating of perceived exertion, La, or body-mass losses between trials.The addition of caffeine to the carbohydrate-electrolyte solution improved sprinting performance, countermovement jumping, and the subjective experiences of players. Caffeine appeared to offset the fatigue-induced decline in self-selected components of performance.